2009
DOI: 10.1007/s10570-009-9331-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose structural arrangement in relation to spectral changes in tensile loading FTIR

Abstract: In order to utilise wood and wood fibres in advanced materials, a better understanding of the mechanical material characteristics and the interactions among the components is necessary. For this purpose, FTIR was explored together with mechanical loading as a means of studying the molecular responses to the loading of spruce wood and cellulose paper material. A linear shift of absorption bands was detected as the loading was applied. In relation to the applied stress these shifts were higher under moist condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 22 publications
8
66
0
4
Order By: Relevance
“…Tight lateral binding is facilitated by the hydrogen-bonding pattern of the surface chains, at only a small cost in tensile stiffness due to the loss of intramolecular hydrogen bonding between O2 and O6 (81). The surface location of these disordered chains means that a parallel mechanical model with tight lateral bonding to the ordered core is more appropriate than a series model, consistent with FTIR observations (35). The twisting of adjacent microfibrils may explain why they do not come into crystallographic register with one another over enough of their length to coalesce.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Tight lateral binding is facilitated by the hydrogen-bonding pattern of the surface chains, at only a small cost in tensile stiffness due to the loss of intramolecular hydrogen bonding between O2 and O6 (81). The surface location of these disordered chains means that a parallel mechanical model with tight lateral bonding to the ordered core is more appropriate than a series model, consistent with FTIR observations (35). The twisting of adjacent microfibrils may explain why they do not come into crystallographic register with one another over enough of their length to coalesce.…”
Section: Discussionsupporting
confidence: 64%
“…The diameter of the cellulose fibrils and the proportion of crystalline material are key inputs into our understanding of the mechanical performance of cellulose (34)(35)(36) and into calculations of the strength of wood, textile fibers, and cellulose-based nanocomposite materials (37,38). In addition cellulose "crystallinity" and aggregation control accessibility to glucanase enzymes (39) and are thus important but rather poorly defined questions in the technology of liquid biofuel production from cellulosic biomass.…”
mentioning
confidence: 99%
“…. Absorption spectra of the C-O-C vibration peak with increasing stress levels [35] Polarized FTIR accompanied with a vapor-phase deuteration has been used to characterize orientation of the main chains and hence to study the molecular orientation of Nematic Ordered Cellulose (NOC) [36]. A ratio (R) of the absorbance of the band due to the particular molecular moiety for radiation polarized perpendicular to to parallel to the stretching direction was introduced to evaluate the orientation behaviour of the main chains and OH groups.…”
Section: Structure Of Natural Fibres Determined By Using Ftirmentioning
confidence: 99%
“…It is well known that moisture cannot access the crystalline regions of the cellulose, which is why the structural arrangement of these in the fibril structure must be of great importance. Molecular deformation studies (Salmén and Bergström 2009) clearly showed that the hygroscopically accessible regions of the carbohydrates are mostly arranged in a parallel arrangement with the cellulose crystalline areas, see Fig. 5.…”
Section: Cellulose Propertiesmentioning
confidence: 95%
“…So far, studies on a microlevel regarding stress transfer when loading wood fibres have not been able to demonstrate whether lignin makes much of a contribution. Raman and FTIR measurements of stress deformation in lignin have been unsuccessful in detecting a straining of the lignin molecule, even with very high stresses on the cellulose molecules themselves (Gierlinger et al 2006;Salmén and Bergström 2009). Here, one could make an argument about the suitability of the method itself, i.e.…”
Section: Lignin Propertiesmentioning
confidence: 99%